2009
DOI: 10.1111/j.1529-8019.2009.01276.x
|View full text |Cite
|
Sign up to set email alerts
|

Original Article: Superficial cutaneous fungal infections in tropical countries

Abstract: Superficial fungal infections represent an important cause of morbidity for people worldwide, particularly in the tropics. Fungal infections affect the skin, hair, or the nails, and tend to thrive in the heat and humidity of tropical countries. Because of environmental and cultural factors unique to the tropics, the causative organisms and presentation of these infections may differ from those in industrialized countries. Treatment options include topical and systemic therapy. However, social and socioeconomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…This agrees with the reports of El Sayed et al, [20] and Souza et al [21]. Souza et al [21] reported that 72.25% of cases of onychomycosis from their study in Japan were among females, while Kazemi [22] and Charles [23] reported higher prevalence of this infection among males, even though their studies were not among rice farmers. This is also supported by the findings of Blank et al [24] and Shenoi et al [8] who reported a high rate of nail infection among paddy field workers in India.…”
Section: Discussionsupporting
confidence: 78%
“…This agrees with the reports of El Sayed et al, [20] and Souza et al [21]. Souza et al [21] reported that 72.25% of cases of onychomycosis from their study in Japan were among females, while Kazemi [22] and Charles [23] reported higher prevalence of this infection among males, even though their studies were not among rice farmers. This is also supported by the findings of Blank et al [24] and Shenoi et al [8] who reported a high rate of nail infection among paddy field workers in India.…”
Section: Discussionsupporting
confidence: 78%
“…1-4,11-14,16,17,24 It has exclusive action against dermatophytes and acts by interfering with DNA synthesis. Griseofulvin is better absorbed in the form of microcrystals and in the presence of fat.…”
Section: Othermentioning
confidence: 99%
“…However, the same commensal microbial species are also implicated in the pathogenesis of cutaneous infections under altered micro-environmental conditions or when able to overcome the host immune systems [13], as well as in proinflammatory diseases such as acne vulgaris [14], atopic dermatitis [15], and psoriasis [16]. Upon penetration of the skin barrier, members of the skin microflora have been known to elicit diseases such as impetigo, cellulitis, and systemic diseases including endocarditis and sepsis [17].…”
Section: Introductionmentioning
confidence: 99%